On the occurrence of Riccardoella limacum (Schrank, 1781) (Acari, ereynetidae) in escargot farms in Brazil - Flechtmann, Carlos H.W.; Baggio, Domingos (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1985)
The slug-mite, Riccardoella limacum (Schrank) is reported from Helix aspersa L. and H.pomatia L. farms in Belo Horizonte, Minas Gerais and in Embu, São Paulo, Brazil. Death of escargots is correlated with the presence of high numbers of this mite.